2018
DOI: 10.1016/s1470-2045(17)30777-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes for neoadjuvant versus adjuvant chemotherapy in early breast cancer: meta-analysis of individual patient data from ten randomised trials

Abstract: SummaryBackgroundNeoadjuvant chemotherapy (NACT) for early breast cancer can make breast-conserving surgery more feasible and might be more likely to eradicate micrometastatic disease than might the same chemotherapy given after surgery. We investigated the long-term benefits and risks of NACT and the influence of tumour characteristics on outcome with a collaborative meta-analysis of individual patient data from relevant randomised trials.MethodsWe obtained information about prerandomisation tumour characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
443
2
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 832 publications
(498 citation statements)
references
References 28 publications
13
443
2
9
Order By: Relevance
“…Studies have shown a significant increase in pathological response in primary breast cancer patients when docetaxel was given as sequential therapy with doxorubicin and cyclophosphamide in a neo‐adjuvant setting . Safety of NACT is comparable with adjuvant chemotherapy in several randomized trials . These findings have encouraged the use of docetaxel in neo‐adjuvant settings.…”
Section: What Is Known and Objectivementioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown a significant increase in pathological response in primary breast cancer patients when docetaxel was given as sequential therapy with doxorubicin and cyclophosphamide in a neo‐adjuvant setting . Safety of NACT is comparable with adjuvant chemotherapy in several randomized trials . These findings have encouraged the use of docetaxel in neo‐adjuvant settings.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…6 Safety of NACT is comparable with adjuvant chemotherapy in several randomized trials. 7 These findings have encouraged the use of docetaxel in neo-adjuvant settings. NACT followed by surgery and adjuvant radiation therapy is the standard care of treatment for patients with locally advanced breast cancer (LABC).…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%
“…It has been shown that the desired tumor size reduction is not accomplished with NAC in up to 31% of patients who will have stable or even progressive disease. 4 In order to identify patients who will have stable or progressive disease, it is important to identify biomarkers that can assess the response to NAC at an early stage in the individual patient. This could enable the adjustment of systemic therapy and avoid toxicity and the related costs of ineffective treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The outgrowth of primary luminal breast cancer (BCa) is driven by nonmutated estrogen receptor α (ERα), with all patients receiving adjuvant endocrine therapy after curative surgery (ET). This strategy significantly delays clinical relapse but does not abrogate it completely, as about ~3% of the patients each year come back with overt relapse, inevitably leading to further metastatic development [1][2][3] . The frequency of relapse remains constant up to 20 years after surgery making ETresistance the most critical clinical problem for the management of these patients 4 .…”
Section: Introductionmentioning
confidence: 99%